In Reply. (2nd November 2016) - Brandi, Giovanni; Deserti, Marzia; Vasuri, Francesco; Farioli, Andrea; Degiovanni, Alessio; Palloni, Andrea; Frega, Giorgio; Barbera, Maria A.; de Lorenzo, Stefania; Garajova, Ingrid; Di Marco, Mariacristina; Pinna, Antonio D.; et al.
Abstract : Brandi et al. clarify data about the localization of human equilibrative nucleoside transporter 1 in cancer patients receiving gemcitabine-based chemotherapy. They discuss methodology, differences between antibodies, and recommendations for further study.